Effect of Black Soybean (Glycine soja) Extract on Ovarian Histology of Swiss Webster Mice (Mus musculus L) Unilateral Ovariectomy - Mahriani, Mahriani; Utami, Eva Tyas; Primasari, Nindita Fitria (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2022)
Estrogen production can be reduced due to menopause and ovariectomy. Decreased estrogen levels in the body cause physiological changes in the female reproductive system. Therefore, the intake of estrogen from outside the body is needed, in this case phytoestrogens from soy bean extract can be used to replace the role of endogenous estrogen. The study used 30 Swiss Webster mice (Mus musculus) aged 90 days weighing 35 grams which were unilateral ovariectomy. Mice are ready to be used as test animals after an estrogen deficiency period of 60 days. Mice are ready to be used as test animals after an estrogen deficiency period of 60 days. Mice were divided into five groups: negative control, positive control, dose 0.21, 0.42, and 0.63 g/mL/day . Data obtained from the results of the study were analyzed using the One Way ANOVA test with a confidence level of 99% or α = 0.01. Based on the results of the study, the administration of black soybean flour extract in unilateral ovariectomy mice can increase the average number of primordial follicles at doses of 0.42 g/ml/day and dosage 0.63 g/ml/day, primary follicles at a dose of 0.42 g/ml/day and doses of 0.63 g/ml/day, and secondary follicles at a dose of 0.63 g / ml / day, and tend to increase the average number of primordial follicles at doses of 0.21 g/ml/day, follicles primary at doses of 0.21 g/ml/day, secondary follicles at doses of 0.21 g/ml/day and 0.42 g/ml/day, de Graaf follicles at doses of 0.21, 0. 42 and 0.63 g/ml/day.